POLA DISTRJBUSI BENIH PADI BERSUBSIDIDI KABUPATEN PURBALINGGA - Utami, Pujiati (Jurnal Ilmu-Ilmu Pertanian, 2011)
This research aim to propose an alternative distribution pattern of government- subsidized paddy seeds to effictively reach the farmers. The research was conducted in Purbalingga District, Central Java, by using the descriptive analysis method. The primary and secondary data were obtained by indepth interview and documentation. The data were further analysed descriptively to lonw the mechanism of subsidize paddy seeds distribution. Result of the research indicated that the paddy seed varieties (breeder seeds) were first yielded by the Ministry of Agriculture's Reseqrch and Development Center, then further distributed b Seed Directorate to be channelled to Balai Benih Induk, the institution responsible for yielding the foundation seeds. The seeds w-ere then propagated by producers and middlemen to yield stock seeds or extension seeds and became available to the farmers through agriculture kiosks.